Penerapan Teknik Bercerita Dua Arah (Two-Way Storytelling) untuk Meningkatkan Kemampuan Menyimak Anak Kelompok B di TK PGRI 07 Aikmel - Fadila Sadida; Muhammad Tahir; Baiq Nada Buahana; Fahruddin (Mataram University, 2026)
This study aimed to improve the listening skills of Group B children at TK PGRI 07 Aikmel through the implementation of the two-way storytelling technique. The study was motivated by the low listening skills demonstrated by the children, as reflected in their limited attention during storytelling activities, difficulties in answering questions related to the story, and inadequate ability to comprehend and retell information in a sequential manner. This research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles involving planning, action, observation, and reflection stages. The participants were Group B children of TK PGRI 07 Aikmel. Data were collected through observation and documentation using an assessment instrument covering attention focusing, story comprehension, question answering, relevant responses, and following sequential instructions. The data were analyzed using descriptive qualitative and quantitative techniques, with a classical success criterion of at least 85%. The findings revealed a continuous improvement in children’s listening skills across the cycles. The percentage increased from 64.48% in the pre-cycle to 75.71% in Cycle I and reached 86.06% in Cycle II, exceeding the predetermined success criterion. These findings indicate that the implementation of the two-way storytelling technique is effective in improving the listening skills of early childhood learners. Furthermore, the study highlights the pedagogical value of interactive storytelling in promoting active participation, language development, and meaningful learning experiences among young children.